Predictive value of intratumour inflammatory cytokine mRNA levels of hepatocellular carcinoma patients and activation of two distinct pathways govern IL-8 induced epithelial-mesenchymal transition in human hepatic cancer cell lines. (July 2019) - Peng, Siqi; Chen, Yutong; Gong, Yihang; Li, Zizi; Xie, Rongzhi; Lin, Yujing; Zou, Baojia; Li, Jian; Zeng, Linjuan
Graphical abstract: Highlights: High expression level of intratumoural IL-8 mRNA predicts poor prognosis in HCC patients. Intratumoural IL-8 mRNA expression positively correlates with SNAI1 and TWIST1 mRNA expression. IL-8 induces EMT of HCC cells via IL-8/ERK1/2/SNAI1 and IL-8/STAT3/TWIST1 signalling pathways. Abstract: Hepatocellular carcinoma (HCC) is always accompanied by persistent inflammation of liver tissues, which is considered to exert protumourigenic effects by promoting cancer growth, progression, and metastasis. However, the tumour-promoting roles and predictive value of intratumoural inflammatory cytokines remain unclear. In the present study, we used database analysis, clinical pathological studies, and in vitro biological experiments on human hepatic cancer cell lines to assess the prognostic potential of the primary tumour cytokine mRNA levels and underlying mechanisms in HCC. First, we assessed the prognostic value of several cytokines from the TCGA database and found that IL-8 is a unique cytokine that is associated with poor overall survival of HCC patients. Then, we collected 87 HCC tumour and adjacent non-tumour specimens from patients and confirmed that patients with low IL-8 expression exhibited less intrahepatic invasion or distant metastasis, a lower recurrence rate and longer overall survival time compared to patients with high IL-8 expression. Wound healing, transwell, and western blotting assay results showed that IL-8 promotes the migration and invasion of Huh-7 and HepG2 cells, and the underlying mechanism is that IL-8 induces the EMT of HCC cells via the IL-8/ERK1/2/SNAI1 and IL-8/STAT3/TWIST1 signalling pathways. These results provide valuable biological IL-8 information which needs to be further investigated in liver cancer target therapy research. Furthermore, the intratumoural cytokine expression at the mRNA level may provide insight into hepatocarcinoma prognosis.